Associations between physical activity and health-related fitness – volume versus pattern. Issue 6 (19th March 2017) - Knaeps, Sara; Bourgois, Jan G.; Charlier, Ruben; Mertens, Evelien; Lefevre, Johan
ABSTRACT: Approximately 3.2 million people die of non-communicable diseases (NCD) each year due to insufficient physical activity. Physical activity guidelines are possibly perceived as too demanding and might thus pose a barrier. We addressed the question if a more stable physical activity pattern is associated with higher levels of health-related fitness than one with high and low intensities, regardless of the physical activity level (PAL). Physical activity was objectively measured in 296 men and women (53.7 ± 8.94 years) with the SenseWear Pro Armband ® . Using this data, the PAL and a Gini index were calculated to report the physical activity pattern. Health-related fitness was expressed as a fitness index. PAL was weakly correlated to health-related fitness ( r  = 0.38, P  < .0001). The Gini index was also weakly correlated to the fitness index ( r  = 0.23, P  < .0001). Results of the ANCOVA showed that participants in the first quartile of PAL always scored significantly lower for health-related fitness than participants in quartile four, after adjustment for the Gini index. These results suggest that as long as the volume of physical activity is high, health-related fitness will be high as well, independent of the physical activity pattern or variability in intensities throughout the day.